Reference equations for impulse oscillometric and respiratory system model parameters in anglo and hispanic children - Meraz, E. G.; Nazeran, H.; Edalatpour, E.; Rodriguez, C.; Montano, K.; Aguilar, C.; Avila, N.; Vidaña, J. O.; Portillo, A. L. (Revista Mexicana de Ingenieria Biomedica, 2016)
The Impulse Oscillometry System (IOS) has been recognized as a useful diagnostic tool. Previous research by our group has shown that R5 (Resistance at 5 Hz), R5-R20 (frequency dependence of resistance), AX (the ``Goldman Triangle’’) and the extended Resistor-Inductor-Capacitor (eRIC) model-derived parameter Cp (peripheral Compliance) are reliable measures that track respiratory system function. Here we determined the predictive equations from 112 asthmatic and non-asthmatic Anglo and Hispanic children data, that were previously classified into four groups: Normal, PSAI (Probable Small Airway Impairment), SAI (Small Airway Impairment), and Asthma by using regression analysis of IOS and eRIC model parameters as dependent variables regressed against age, height, and weight. Height showed the greatest correlation with IOS and eRIC model parameters and provided the most significant reference values for these measures in Anglo and Hispanic children. These values could serve as a useful framework for diagnosis, early interventions, and treatment of respiratory diseases in this population.